Characterization of the Antimicrobial Edible Film Based on Grasshopper Protein/Soy Protein Isolate/Cinnamaldehyde Blend Crosslinked With Xylose - Zhang, Zisen; Zhou, Xing; Fang, Changqing; Wang, Dong (Frontiers in Nutrition, 2022)
A composite material based on a new insect-based grasshopper protein (GP)/soy protein isolate (SPI) blend has been studied by solution casting using xylose as a crosslinker and cinnamaldehyde (CIN) as an antimicrobial agent to develop a novel antimicrobial edible packaging. In this paper, the effects of SPI, xylose and CIN content on the properties of edible film was studied. The tensile test confirmed that 30% SPI incorporation content had the best blending effect with mechanical properties and barrier properties improving obviously. After adding 10% xylose to form crosslinking network, the tensile strength and elongation at break of the film showed the best state increasing to 3.4Mpa and 38%, respectively. The 30% CIN enabled the film to be resistant to E. coli and S. aureus strongly and decreased the water vapour permeability to 1.8×10-11(g/cm·s·Pa) but had a negative effect on mechanical properties. This is the first time that edible insects have been used to produce natural edible antimicrobial packaging, proving edible insects, an excellent protein source, tipped to be a potential source of raw materials for biomaterials.